2008
DOI: 10.1159/000156478
|View full text |Cite
|
Sign up to set email alerts
|

Variation Rhythms of Lymphocyte Subsets during Healthy Aging

Abstract: Immunological alterations associated with aging (immunosenescence) do not represent a simple unidirectional decline in all functions but develop as a complex remodeling of the immune system, involving multiple reorganization and developmentally regulated changes. In general, most data available about aging were obtained at particular age intervals and most of them come from Caucasian individuals from either Europe or the United States. Here, we report the frequencies of major lymphocyte subsets in healthy Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…It is the first report describing changes in the profile of cytokine-producing leukocytes in Brazilian individuals within a large spectrum of age (0–85 years). These findings are an extension of another study from our group [34] that analyzed the frequency of sub-populations of leukocytes in Brazilian individuals at similar age range (0–85 years).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…It is the first report describing changes in the profile of cytokine-producing leukocytes in Brazilian individuals within a large spectrum of age (0–85 years). These findings are an extension of another study from our group [34] that analyzed the frequency of sub-populations of leukocytes in Brazilian individuals at similar age range (0–85 years).…”
Section: Discussionsupporting
confidence: 76%
“…These cells showed a decreased production of TNF-α and IL-10 in adults and in the elderly group [12, 56, 57]. Our group has observed that frequencies of B-cells decline in Brazilian individuals of 19–40 age group and these data is compatible with the lower percentage of cytokine-positive B-cells in adulthood [34]. …”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations